CALCULATION OF THE EFFECTIVE MASS TRANSFER AREA IN TURBULENT CONTACT ABSORBER - DRĂGAN, Simion (Studia Universitatis Babeș-Bolyai Chemia, 2016)
One of the most important efficiency parameters for separation columns is the effective interfacial mass transfer area. In this study the effective mass transfer area in gas-solid-liquid turbulent contact absorber was determined using the chemical absorption of carbon dioxide into sodium hydroxide aqueous solution. The effective mass transfer area determined in this study was found to be from three to six times higher than the geometric area of the solid packing.